Optimization of sugar production from cassava residue using response surface methodology - Mohd Shahril, Mustafa@Sulaiman (2010)
Cassava residue,starch processing waste from cassava starch plant,was used as a raw material in sugar production.This is study aims to optimize the production of sugar from cassava residue using response surface methodology.The effect of parameters such as incubation time and enzyme concentration is used to study the concentration of glucose produced. Three different enzymes are used to produce glucose namely cellulase,glucoamylase and α-amylase.Cellulase was the best enzyme that yielded the most glucose.The optimization of the production of sugar is carried out by using response surface methodology (RSM) based on the central composite design (CCD).The optimal set parameters for enzyme concentration are 1.32 g/mL and 4.47 hours of incubation time.Glucose concentration of 1.059 g/L was achieved by using these optimal parameters.